Autonomia re-imaginada: Autonomy Re-Imagined - Cornell, Drucilla; Beltrão, Igor; Pimentel Fischer Pacheco, Mariana (Revista Direito e Práxis, 2024)
DOI: http://doi.org/10.1590/2179-8966/2024/79726 Tradução: Igor Beltrão Castro de Assis: E-mail: ibeltraoca@gmail.com. ORCID: https://orcid.org/0000-0003-4296-6076. Mariana Pimentel Fischer Pacheco: E-mail: marianafisch@gmail.com. ORCID: https://orcid.org/0000-0003-3217-5756.